Ancient Runoff Harvesting Agriculture in the Hyper‐Arid Uvda Valley of Israel: An Agro‐Hydrological Assessment. (25th May 2017) - Stavi, Ilan; Shem‐Tov, Rahamim; Ragolsky, Gidon; Lekach, Judith
Abstract: Archaeological surveys conducted since the 1980s in the hyper‐arid Uvda Valley of southern Israel revealed extensive lands with runoff harvesting systems for growing barley and wheat during ancient times. Despite the impossibility of dating the earth and stone installations of terraces and limans due to their decay over time, a wealth of ancient agricultural tools located across the valley revealed inhabitation between the Late Neolithic, Chalcolithic, and Early Bronze ages. Also, cropping of barley in the valley's runoff harvesting systems took place until the 1950s by local Bedouin populations. The objective of this study was to assess the valley's agronomic potential under current climatic conditions. This was assessed by the analysis of precipitation (P) and reference evapotranspiration (ETo ) data for the rainy seasons during a 17‐year period between 1999–2000 and 2015–2016. Using the ETo data and the single crop coefficient (Kc ) for barley and wheat allowed the calculation of crop evapotranspiration (ETc ) and the seasonal soil water deficit (D). Hydrological assessment of the valley's basin allowed the calculation of potential runoff volumes which could be available for agricultural use on the valley floor. Overall, the results showed a potential for successful cereal cultivation only in one to two years during this 17‐year period. This revealed no viability for local agriculture under current climatic conditions. Insights from this study consist with other studies which indicated considerably drier climatic conditions at present compared to those in ancient times, and even compared to those in the mid‐twentieth century. Copyright © 2017 John Wiley & Sons, Ltd.